Analisis Keragaman Genetik Dyera costulata (Miq) Hook.f. Berdasarkan Marka â€œRandom Amplified Polymorphic DNAâ€ - Poerba, Yuyu Suryasari; Widjaya, Elizabeth A. (Universitas Atma Jaya Yogyakarta, 2010)
Dyera costulata (Miq.) Hook.f (Apocynaceae) is a large tree of the lowland tropical rain forest of Southeast Asia that occurs in Thailand, the Malay Peninsula and on the islands of Sumatera and Borneo. Its economic value was in its latex, used as gum chile in the manifacture of chewing gum. Nowadays the timber of this species is largely utilized for the manufacture of pencils and picture frames. The information on genetic diversity of the species is very limited. Hence studies were initiated and genetic diversity were estimated using Random Amplified Polymorphic (RAPD) markers in 47 accessions of Dyera costulata procured from different geographical regions of Jambi. Four selected Operon primers (10 mer) generated a total of 90 consistent amplification products ranging from 150 bp to 2.8 Kb. The cluster analysis showed that the 47 individuals were separated into one main cluster and one individual. The range of genetic dissimilarity value among samples was from 0.06 to 0.71, while genetic distance among populations was from 0.17 to 0.42. These values showed that those 47 accessions of D. costulata from Jambi was genetically originated from diverse population.